Snubberless voltage sharing of series-connected insulated-gate devices by a novel gate control strategy. - Belverde, G.
Insulated gate devices, such as metal oxide semiconductor field effect transistors (MOSFETs) or insulated gate bipolar transistors (IGBTs), are increasingly used in high-voltage power converters where a request for fast power switches is growing. Series connection of devices is a viable approach to manage voltages higher than the blocking voltage of the single device. The main problem in such an application is to guarantee the voltage balance across the devices both in steady-state and during switching transients. In this paper, a novel approach is presented, which is used to equalize the voltage sharing during the switching transients. The main advantages of the proposed method consist in avoiding the traditional use of the snubber capacitors, in the output power side, and in working on the gate side. The application of the proposed gate drive technique is firstly discussed and compared with different solutions, hence, validated by experimental tests applied to the control of series connected devices. Finally, a comparison is performed between the transient behaviors of two different configurations: a single switch with high-voltage blocking capability, and in alternative a series of two devices which together ensure the voltage blocking capability of the single switch. The better performances of the latter configuration, working with the proposed control circuit, over the former have been experimentally demonstrated
Keywords: Fast power switches; Gate control strategy; High-voltage power converters; Power IGBTs; Power MOSFETs; Series-connected insulated-gate devices; Snubberless voltage sharing; Steady-state.; Switching transients; Voltage balance; Voltage blocking capability